Dendrimer Conjugation Enables Multiphoton Chemical Neurophysiology Studies with an Extended π‐Electron Caging Chromophore. (19th July 2019) - Richers, Matthew T.; Passlick, Stefan; Agarwal, Hitesh; Ellis‐Davies, Graham C. R.
Abstract: We have developed a caged neurotransmitter using an extended π‐electron chromophore for efficient multiphoton uncaging on living neurons. Widely studied in a chemical context, such chromophores are inherently bioincompatible due to their highly lipophilic character. Attachment of two polycarboxylate dendrimers, a method we call "cloaking", to a bisstyrylthiophene (or BIST) core effectively transformed the chromophore into a water‐soluble optical probe, whilst maintaining the high two‐photon absorption of over 500 GM. Importantly, the cloaked caged compound was biologically inert at the high concentrations required for multiphoton chemical physiology. Thus, in contrast to non‐cloaked BIST compounds, the BIST‐caged neurotransmitter can be safely delivered onto neurons in acutely isolated brain slices, thereby enabling high‐resolution two‐photon uncaging without any side effects. We expect that our cloaking method will enable the development of new classes of cell‐compatible photolabile probes using a wide variety of extended π‐electron caging chromophores. Abstract : Das „Verhüllen" eines ansonsten wasserunlöslichen, photoaktivierbaren Neurotransmitters mit einem Dendrimer (siehe Molekülstruktur) verleiht Wasserlöslichkeit, schützt Neuronen vor Toxizität, verhindert Rezeptorantagonismus und ermöglicht eine Multi‐Photonen‐Photoaktivierung für chemisch‐physiologische Studien in lebenden Gehirn‐Gewebeschnitten.